Analisis Dinamis Hubungan Antara Kepadatan Penduduk, PDRB Per Kapita, dan Ketimpangan Wilayah di Indonesia - Yulikasari Yulikasari; M. Afdal Samsuddin (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to analyze the dynamic relationship between population density, Gross Regional Domestic Product (GRDP) per capita, and regional economic inequality in Indonesia over the period 1995–2024. Regional inequality is measured using the Gini Ratio as a key indicator. A quantitative method with a time series approach is employed using the Vector Autoregression (VAR) model. The analysis includes unit root testing, optimal lag selection, VAR estimation, impulse response function (IRF), variance decomposition, and Granger causality testing. The results show that population density has a positive effect on regional inequality, while GRDP per capita has a negative effect. However, both variables are statistically insignificant. The impulse response analysis indicates that a shock in population density tends to increase inequality in the short term, whereas a shock in GRDP per capita tends to reduce inequality. The Granger causality test reveals that population density regional inequality, while GRDP per capita does not have a significant causal effect. Overall, the findings suggest the importance of equitable economic development and population control policies in reducing regional disparities in Indonesia.